У центрі уваги – митець: творення та виконання традиційних казок - Дег, Л. (Народна творчість та етнологія, 2012)
Linda Degh. The Artist at the Center: Creating and Performing Traditional Tales. Telling stories is a traditional skill. The study of folk narratives has a big diversity of approaches, yet the ethnographic observation-based study of the creative process of narration has barely begun. Folklorists experimented with borrowed methods focusing mostly on texts, without building a systematic research approach for their discipline. The tale exists only when it is told, and it is told differently every time someone tells it. Still, scholars rejected the idea of listening to tellers, they prefer to use reworked texts. I am one of few who built a theory of oral narration on the basis of the narrator’s creativity, the artist at the center.